Exploring the legal implications of the Trips trademark rules on the consumers' right to health in Africa - Akonumbo, Atangcho Nji (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2007.